(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2024)
Background: Throughout the world in 2019 there were 2.7 million cases of perineal rupture in mothers giving birth. This figure is estimated to reach 6.3 million in 2050. In Indonesia, 75% of mothers who give birth vaginally experience perineal wounds. In 2023, the number of postpartum mothers and perineal ruptures in December was 311 postpartum mothers, of which 180 experienced perineal rupture and 131 did not experience rupture.. Objektive: The general aim of this research is to analyze the relationship between knowledge and attitudes of postpartum mothers towards perineal wound care at RSIA Paradise Tanah Bumbu. Methods: The research method used uses analytical research. By using an analytical research design. The method used is a cross-sectional approach, which is a study to study the dynamics of the correlation between factors. The total sampling technique is a sampling technique where the number of samples is the same as the population, namely 30 people, knowledge questionnaire sheets and the attitudes of postpartum mothers towards perineal wound care. Results: This is shown by the Pearson Chi-Square value of 30,000 with a significance value of 0.000. This is shown by the Pearson Chi-Square value of 26.218 with a significance value of 0.000 Conclusion: There is a relationship between knowledge and perineal wound care and there is a relationship between attitude and perineal wound care.